2021
DOI: 10.3390/su13169395
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Social Responsibility on Poverty

Abstract: Being one of the open social innovations of business entities, social responsibility is taking an important role in our society. It not only contributes to the improvement of the financial indicators of business entities, but also has a significant impact on the economic development of countries and the creation of well-being of the society members. The business contribution to environmental and social initiatives influences various economic processes and, at the same time, affects the level of poverty in coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 102 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…Programs in the SR area stimulate the improvement of health, the environment, and involvement in educational activities, acting as an essential mechanism for mediating between the organization’s ethical practices and improving employees’ and communities’ WB [ 110 ], as demonstrated by the confirmation of the validity of Hypothesis H3. Companies are increasingly recognizing the strategic importance of OE and SR in ensuring employees’ WB and the sustainability of their business [ 69 , 84 , 86 ], as well as employee satisfaction in implementing SR programs and ethical conduct. Organizations that promote health and safety management practices and ensure an adequate work environment [ 88 ] benefit from increased employee engagement, as the organization demonstrates an interest in employees’ WB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Programs in the SR area stimulate the improvement of health, the environment, and involvement in educational activities, acting as an essential mechanism for mediating between the organization’s ethical practices and improving employees’ and communities’ WB [ 110 ], as demonstrated by the confirmation of the validity of Hypothesis H3. Companies are increasingly recognizing the strategic importance of OE and SR in ensuring employees’ WB and the sustainability of their business [ 69 , 84 , 86 ], as well as employee satisfaction in implementing SR programs and ethical conduct. Organizations that promote health and safety management practices and ensure an adequate work environment [ 88 ] benefit from increased employee engagement, as the organization demonstrates an interest in employees’ WB.…”
Section: Discussionmentioning
confidence: 99%
“…Researching employees’ perceptions and attitudes towards SR, OE, and WB is important [ 34 , 84 , 85 ] because it can lead to seeking opportunities for better implementation of responsible and ethical social practices and initiatives. In addition, companies are increasingly recognizing the strategic importance of OE and SR in ensuring employees’ WB and the sustainability of their business [ 69 , 84 , 86 ], as well as employee satisfaction in implementing SR programs and ethical conduct.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, heterogeneous results also show that registered households (groups that receive government subsidies) are more supportive of waste classification policies, suggesting that the Chinese Government will get more environmental benefits in return for helping the poor. In the existing literature, Listyaningsih, et al [69] explored that poverty alleviation plans can be implemented through poverty level detection, Leadley, et al [70] showed that poverty can lead to occupational deprivation and occupational inequity, with lifelong impacts on individuals' health and well-being, Jakunskiene [71] explored the relationship between poverty and social responsibility, but there are few discussions on the relationship between poor populations and environmental benefits. Therefore, the findings of this study provide new evidence for discussing the environmental welfare effects of poverty management.…”
Section: Discussionmentioning
confidence: 99%